"I don't want to let myself down or the charity down": men's accounts of using various interventions to reduce smoking and alcohol consumption. Issue 1 (2nd January 2018) - Allmark, Nigel; Grogan, Sarah; Jeffries, Mark
ABSTRACT: Men are less likely to seek medical help than women and are more likely to adopt unhealthy practices. This study investigated men's constructions of alcohol and tobacco cessation interventions in relation to dominant masculine identities. Focus groups and interviews with 12 male university students were analysed using an eclectic approach informed by discursive psychology and Foucauldian discourse analysis. Findings suggested that interventions encouraging competition among friends were constructed as favourable, and autonomy and control were central to men's accounts. While men presented their behaviour change as intentional, their accounts revealed a tendency to conceal this from others, suggesting a negative influence of peer pressure. However, participants who had raised money for charity whilst abstaining described this process as rewarding and acting as a "buffer" to legitimise their healthy behaviour when socializing with other men. Implications for health providers and policy makers are discussed.